The Effect Of Green Culture And Csr On Financial Performance With XBRL Application As Moderating Variables - Selfiani, Selfiani; Yunita, Irma (CV. Inara, 2022)
This study aims to examine the effect of green culture and CSR on financial performance with the application of XBRL as a moderating variable. This research method uses quantitative and secondary data. The sample used in this study is manufacturing companies listed on the IDX in 2020 with the measurement of financial performance variables using the ROA formula, green culture using an index, CSR using an index, and the implementation of XBRL using an index. The stages for the analysis method are descriptive statistics analyzing the mean, minimum, maximum and standard deviation; assumption test: assumption of normality, assumption of absence of multicollinearity symptoms, assumption of autocorrelation, and assumption of heteroscedasticity; the normality test of the data, namely the Kolmogrof-Smirnov statistical test; determinant coefficient (R2); and hypothesis testing. The results show that green culture has a positive effect on financial performance, CSR has a positive effect on financial performance, the application of XBRL strengthens the relationship between green culture and financial performance, the application of XBRL strengthens the relationship between CSR and financial performance.